Angle Class II correction with MARA appliance - Kelly Chiqueto; José Fernando Castanha Henriques; Sérgio Estelita Cavalcante Barros; Guilherme Janson (Dental Press Editora, 2013)
OBJECTIVE: To assess the effects produced by the MARA appliance in the treatment of Angle's Class II, division 1 malocclusion. METHODS: The sample consisted of 44 young patients divided into two groups: The MARA Group, with initial mean age of 11.99 years, treated with the MARA appliance for an average period of 1.11 years, and the Control Group, with initial mean age of 11.63 years, monitored for a mean period of 1.18 years with no treatment. Lateral cephalograms were used to compare the groups using cephalometric variables in the initial and final phases. For these comparisons, Student's t test was employed. RESULTS: MARA appliance produced the following effects: Maxillary growth restriction, no change in mandibular development, improvement in maxillomandibular relationship, increased lower anterior facial height and counterclockwise rotation of the functional occlusal plane. In the upper arch, the incisors moved lingually and retruded, while the molars moved distally and tipped distally. In the lower arch, the incisors proclined and protruded, whereas the molars mesialized and tipped mesially. Finally, there was a significant reduction in overbite and overjet, with an obvious improvement in molar relationship. CONCLUSIONS: It was concluded that the MARA appliance proved effective in correcting Angle's Class II, division 1 malocclusion while inducing skeletal changes and particularly dental changes. OBJETIVO: avaliar os efeitos proporcionados pelo aparelho MARA no tratamento da má oclusão de Classe II, 1ª divisão. MÉTODOS: utilizou-se uma amostra de 44 jovens, divididos em dois grupos - Grupo MARA, com idade inicial média de 11,99 anos e tratado com o aparelho MARA por um período médio de 1,11 ano; e Grupo Controle, com idade inicial média de 11,63 ano e observado por um período médio de 1,18 ano, sem nenhum tratamento. Utilizou-se as telerradiografias em norma lateral para comparar os grupos quanto às variáveis cefalométricas das fases inicial e final. Para essas comparações, aplicou-se o teste t de Student. RESULTADOS: o aparelho MARA proporcionou efeitos na restrição do crescimento maxilar, sem nenhuma alteração do desenvolvimento mandibular, com melhora da relação maxilomandibular, aumento da altura facial anteroinferior e inclinação anti-horária do plano oclusal funcional. Na arcada superior, os incisivos foram lingualizados e retruídos, e os molares foram distalizados e inclinados para distal. Na arcada inferior, ocorreu vestibularização e protrusão nos incisivos, e mesialização e inclinação mesial dos molares. Por fim, observou-se uma redução significativa nos trespasses horizontal e vertical, e uma melhora evidente na relação molar. CONCLUSÃO: pode-se concluir que o aparelho MARA foi eficaz na correção da má oclusão de Classe II, 1ª divisão, promovendo alterações esqueléticas e, principalmente, dentárias.